In vivo and in vitro effectiveness of Azadirachta indica-synthesized silver nanocrystals against Plasmodium berghei and Plasmodium falciparum, and their potential against malaria mosquitoes - Murugan, Kadarkarai; Panneerselvam, Chellasamy; Samidoss, Christina Mary; Madhiyazhagan, Pari; Suresh, Udaiyan; Roni, Mathath; Chandramohan, Balamurugan; Subramaniam, Jayapal; Dinesh, Devakumar; Rajaganesh, Rajapandian; Paulpandi, Manickam; Wei, Hui; et al. (Research in veterinary science, 2016)
Malaria transmission is a serious emergence in urban and semiurban areas worldwide, becoming a major international public health concern. Malaria is transmitted through the bites of Anopheles mosquitoes. The extensive employ of synthetic pesticides leads to negative effects on human health and the environment. Recently, plant-synthesized nanoparticles have been proposed as highly effective mosquitocides. In this research, we synthesized silver nanoparticles (AgNP) using the Azadirachta indica seed kernel extract as reducing and stabilizing agent. AgNP were characterized by UV-vis spectrophotometry, SEM, EDX, XRD and FTIR spectroscopy. The A. indica seed kernel extract was toxic against Anopheles stephensi larvae and pupae, LC50 were 232.8ppm (larva I), 260.6ppm (II), 290.3ppm (III), 323.4ppm (IV), and 348.4ppm (pupa). AgNP LC50 were 3.9ppm (I), 4.9ppm (II), 5.6ppm (III), 6.5ppm (IV), and 8.2ppm (pupa). The antiplasmodial activity of A. indica seed kernel extract and AgNP was evaluated against CQ-resistant (CQ-r) and CQ-sensitive (CQ-s) strains of Plasmodium falciparum. IC50 of A. indica seed kernel extract were 63.18μg/ml (CQ-s) and 69.24μg/ml (CQ-r). A. indica seed kernel-synthesized AgNP achieved IC50, of 82.41μg/ml (CQ-s) and 86.12μg/ml (CQ-r). However, in vivo anti-plasmodial experiments conducted on Plasmodium berghei infecting albino mice showed moderate activity of the A. indica extract and AgNP. Overall, this study showed that the A. indica-mediated fabrication of AgNP is of interest for a wide array of purposes, ranging from IPM of mosquito vectors to the development of novel and cheap antimalarial drugs.
Keywords: antimalarika; Anopheles; Plasmodium berghei; Botanical byproducts; Arbovirus; kukla; stříbro; Silver; Pupa; Filariasis; Culicidae; malárie; Azadirachta; Anopheles stephensi; zvířata; Antimalarials; Nanobiotechnology; Plasmodium falciparum; larva; Larva; Metal Nanoparticles; kovové nanočástice; Malaria; Animals